(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Interesting faunistic data on Geometrid moths collected in the Molise region (Central Italy) during 1996-1999 are reported. On the whole 182 species were recorded, 59 of which are new report for the region. Till now the Geometrid species from Molise are 221. Compared with neighbouring regions, Molise fauna is similar to those of Latium (197 species in common), Marche (186 species in common) and Abruzzi (160 species in common). Lepidoptera Geometridae, faunistic records, Molise region, Centra! Italy.